2018
DOI: 10.1101/395780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance evaluation of inverse methods for identification and characterization of oscillatory brain sources: Ground truth validation & empirical evidences

Abstract: Oscillatory brain electromagnetic activity is an established tool to study neurophysiological mechanisms of human behavior using electro-encephalogram (EEG) and magneto-encephalogram (MEG) techniques. Often, to extract source level information in the cortex, researchers have to rely on inverse techniques that generate probabilistic estimation of the cortical activation underlying EEG/ MEG data from sensors located outside the body. State of the art source localization methods such as exact low resolution elect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Like other methods, eLORETA is characterized by strengths and weaknesses [55]. Despite this, it has been reported that compared to other solutions (e.g., minimum norm estimates), the probability of incorrectly detecting an activation is lower for the eLORETA [55]. Furthermore, compared to older versions (e.g., sLORETA), this new update performs better concerning correct localization and visualization, suppressing nonsignificant details in the following reconstruction [53].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Like other methods, eLORETA is characterized by strengths and weaknesses [55]. Despite this, it has been reported that compared to other solutions (e.g., minimum norm estimates), the probability of incorrectly detecting an activation is lower for the eLORETA [55]. Furthermore, compared to older versions (e.g., sLORETA), this new update performs better concerning correct localization and visualization, suppressing nonsignificant details in the following reconstruction [53].…”
Section: Methodsmentioning
confidence: 99%
“…All EEG data were analyzed through the exact low-resolution brain electromagnetic tomography software (eLORETA [52]), a validated device for the investigation of neural networks functional connectivity [32]. The eLORETA, the advanced version of sLORETA, is considered one of the most widely adopted methods among the brain source localization procedures [53][54][55].…”
Section: Eeg Recordings and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions can be found in another recent, more realistic, independent study. 38 Some recent reports providing direct experimental validation for eLORETA can be found, for instance, in Montani et al 39 where eLORETA localizes correctly well-known language-related areas, and in Göschl et al 40 and Buchholz et al 41 where eLORETA correctly localizes somatosensory-motor areas.…”
Section: Eeg Eloreta Analysesmentioning
confidence: 98%
“…The localized brain source resulting from this so-called EEG inverse problem then can be used for a better diagnosis and treatment of mental or neurological disorders such as epilepsy [3], depression [4], and schizophrenia [5]. eLORETA is one of the most accurate methods in localizing a single focal source [6] in comparison with other distributed source estimation techniques such as minimum norm estimation (MNE) [7], weighted MNE (WMNE) [7], lowresolution electromagnetic tomography (LORETA) [8], and standardized LORETA (sLORETA) [9]. Furthermore, eLORETA shows a better performance in suppressing less significant sources and produces less blurred results in comparison with its predecessor the sLORETA technique [9], [10].…”
Section: Introductionmentioning
confidence: 99%